Hierarchical analyses of genetic variation of samples from breeding and feeding grounds confirm the genetic partitioning of northwest Atlantic and South Atlantic populations of swordfish (Xiphias gladius L.) - Alvarado Bremer, Jaime R.; Mejuto, Jaime; Gómez-Márquez, J.; Boán, F.; Carpintero, P.; Rodríguez, J. M.; Viñas, Jordi; Greig, T.W.; Ely, Bert (Journal of Experimental Marine Biology and Ecology, 2005)
16 pages, 3 figures, 2 tables In species with high migratory potential, the genetic signal revealing population differentiation is often obscured by population admixture. To our knowledge, the explicit comparison of genetic samples from known spawning and feeding areas has not been conducted for any highly migratory pelagic fish species. This study examines the geographic heterogeneity of swordfish mitochondrial DNA (mtDNA) lineages within the Atlantic Ocean using 330 base pairs of sequence of the control region from 480 individuals. Hierarchical analyses of sequence variation were conducted to test whether samples from areas identified as the corresponding spawning and feeding grounds for the northwest (NW) Atlantic (Caribbean and Georges Banks-US northeast) and the South Atlantic (Brazil-Uruguay and Gulf of Guinea), were more closely related to each other than to samples from any other region, including the Mediterranean Sea, the Indian Ocean, and the Pacific Ocean. Phylogeographic analyses reveal that swordfish mtDNA phylogeny is characterized by incomplete lineage sorting and secondary contact of two highly divergent clades. However, despite this complex phylogenetic signature, results from an analysis of nucleotide diversity and from an analysis of molecular variance (AMOVA) were for the most part concordant and indicate that NW Atlantic and South Atlantic swordfish belong to separate populations. The mtDNA distinctiveness of NW Atlantic and South Atlantic swordfish populations is indicative of philopatric behavior in swordfish towards breeding and feeding areas. © 2005 Elsevier B.V. All rights reserved This study was funded in part by the Texas Institute of Oceanography, and by the Cooperative Institute for Fisheries Molecular Biology (FISHTEC) NOAA-NMFS (RT/F-1) and is listed as FISHTEC contribution number FT 02-05 (number will be provided after final acceptance). Additional support was provided by IEO-4.03 and Economic Union project DGXIV, MED93-013 Peer Reviewed